Financial and administrative corruption crimes in the private sector under the First Amendment Law of the Integrity and Illicit Gain Commission Law No. 30 of 2019 - Mustafa Rashid, Teacher Marivan (The college of law and political science journal, 2023)
Corruption in the private sector as well as corruption in the public sector pose amajor threat to societies. This led the United Nations to adopt the Convention against&RUUXSWLRQDWWKHEHJLQQLQJRIWKHWZHQW\ÀUVWFHQWXU\*ZKLFKZDVUDWLÀHGE\,UDT7KHIDFWWKDW,UDTVDFFHVVLRQWRDQGUDWLÀFDWLRQRIWKH8QLWHG1DWLRQV&RQYHQWLRQagainst Corruption means that the country is legally bound by its provisions*EHFDXVHUDWLÀFDWLRQRIDQLQWHUQDWLRQDOWUHDW\* by virtue of constitutions and laws*makes it an integral part of the national legal order. However* the Integrity AuthorityAct No. 30 of 2011 did not include provisions to criminalize corruption in the privatesector*EXWWKHÀUVWDPHQGPHQWWRWKH$FWRI2019* which included changing manyof the legal provisions contained therein* as well as changing the name of theAct and making it a law. Among the fundamental amendments introduced by theOHJLVODWXUHDUHWKHFULPLQDOL]DWLRQRIFHUWDLQIRUPVRIÀQDQFLDODQGDGPLQLVWUDWLYHcorruption of non-employees when it comes to government projects. This meansextending criminalization and extending the competence of the Integrity Authorityin important crimes such as bribery and embezzlement to non-employees.